Sustaining the Values of Tertiary Education during the COVID-19 Crisis - Malee Bassett, Roberta (International Higher Education, 2020)
In the rush to respond to the COVID-19 pandemic—eliminating pathways for spreading the virus by closing physical campuses—institutions the world over turned their initial focus toward teaching, and, to a lesser extent, research. This response is important in the first flush of change. It is imperative, however, to maintain a commitment to some core values in tertiary education—such as equity and social responsibility—to ensure stability during and after the crisis.